SME SUSTAINABILITY THROUGH THE ROLE OF SUITABILITY TASKS IN ACCOUNTING INFORMATION SYSTEMS AND INTERNAL CONTROL - Rudiyanto, Rudiyanto; Paniran, Paniran; Yumhi, Yumhi (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2022)
This paper examines the performance of SMEs in Banten by analyzing the impact of the components of the accounting information system (AIS), internal control system (ICS), and task suitability (ST) on their performance. Our analysis uses Partial Least Square estimation based on data from 214 SMEs. The result of this study show that AIS and ST on performance have a symmetrical relationship. But ICS did not significantly correlated with performance. This study uses accounting information systems (AIS) as a strong predictor of organizational performance. The use of AIS can significantly affect the quality of work, including reducing costs. Finally, we conclude that the use of an accounting information system has a positive effect on cost reduction to increase the effectiveness of decision making. We find evidence that the systematic preparation of task-based procedures contributes to relationships of AIS and internal controls to improve performance in SMEs.